A prospective cohort study of the use of the fatty liver index and Fibroscan to determine the prevalence of fatty liver disease in an Irish population. Issue 2 (February 2022) - Rabbitt, Louise A.; McNally, Mairéad; Reynolds, Laura; Hinchion, Kate; Simpkin, Andrew; Scarry, Margaret; Bohan-Keane, Mary; Goulding, Carol
Abstract : Objectives: Rates of nonalcoholic fatty liver disease (NAFLD) are increasing worldwide. The fatty liver index (FLI) is a noninvasive predictor of NAFLD. This prospective cohort study used the FLI to estimate the prevalence of NAFLD in patients attending an Irish Acute Medical Unit (AMU), and assessed the degree of fibrosis in this group using Fibroscan. Methods: Patients attending the AMU over a 3-month period were invited to participate. Patients with excess alcohol consumption or pre-existing liver disease were excluded. Using established FLI cut-offs, 414 participants were grouped into low (FLI ⩽ 30), medium (30 < FLI ⩽ 60) and high (FLI > 60) risk of NAFLD. High-risk patients were offered review including liver stiffness measurement (LSM) and controlled attenuation parameter (CAP) score. Results: A total of 134 patients were at low-risk, 96 at medium-risk and 184 at high-risk of NAFLD. Male sex ( P < 0.0001) and increasing age ( P < 0.0001) were associated with higher risk. Of the 120 high-risk patients who attended follow up, 13 participants had LSM > 7 kPa. Higher FLI scores were associated with higher CAP scores ( P < 0.0001) but did not predict higher LSMs. Fasting glucose and HbA1c were found to be associated with higher LSM. Conclusion: About 44.4% of patients presenting to the AMU were at high risk of NAFLD according to the FLI. Only 10.8% of the high-risk group, and 3% of all those recruited had a LSM > 7 kPa suggesting development of fibrosis.